Beijing's Hutongs : a book and photo exhibition. - Peh, Wei Siew. (2008)
Includes Appendices: Bidding form--Einvite--Einviteprivate--Financial report--Gallery floor plan--Gallery photos--Invitation card--Pagination--Photos on exhibit--Postcard--Poster--Press release--Write up. This report details the tasks involved in bringing to life what began as a sketchy idea on the hutongs of Beijing. It aims to explain the thought processes and methods of execution that took place from the gestation period to the final delivery, in the form of a book and a pictorial exhibition. It explores, by way of retrospection, the challenges and difficulties faced, while at the same time, offering a potential guide that may be useful for future photojournalism projects.